Surgical resection of a squamous cell carcinoma in the perianal region of a 25‐year‐old crossbred American Paint gelding using sharp surgical excision, laser excision and chemotherapy. (9th March 2018) - Poore, L.; Smit, Y.; Duncan, N.; Williams, J.
Summary: A 25 year‐old American Paint gelding was referred to the Onderstepoort Academic Veterinary Hospital with an ulcerated lesion of nonpigmented skin at the right lateral aspect of the perianal region. An infiltrating squamous cell carcinoma was suspected. Surgical excision and ablation with sharp surgical excision and a diode laser was performed although complete excision was not possible due to the tumour location. Intralesional chemotherapy was performed at the completion of the surgical excision and continued in the post‐operative period. Histological examination of the excised lesion confirmed a diagnosis of squamous cell carcinoma and revealed incomplete resection margins at the medial, dorsal and ventral aspects of the surgical site. The surgical site healed uneventfully and a re‐examination at 6 months post‐surgery revealed the gelding to have normal clinical parameters with no perianal lesions.